Cultural studies in graduate programmes in Latin America: The cases of Colombia and Argentina - Irwin, Robert McKee (2012)
In this article we describe the eccentric location of cultural studies in the Latin American academy: while it remains marginal in terms of institutional recognition, it is nevertheless important in terms of the interest it arouses in professors and students alike, and in the amount and quality of publications in the area. The field?s general flexibility appeals both to many established researchers, who employ its methodologies to expand the scope of their investigations, and to many students, who become frustrated with disciplinary rigidity and with the difficulty in carrying out academic projects with overtly political underpinnings from the traditional disciplines of the humanities and social sciences. While student demand is clearly strong in much of Latin America, the response to the rise of cultural studies in the Latin American academy has taken two general forms: 1) an opening up of spaces within existing disciplines (anthropology, communications, literature, etc.) for the more interdisciplinary or politicized work; 2) the foundation of new programs in cultural studies. We use as examples the case studies of Argentina and Colombia, countries that have a completely different academic history and tradition. We survey the diverse ways in which cultural studies has entered institutional spaces in both countries. Colombia offers the case of an academy that appears to have welcomed the institutionalization of cultural studies, at least superficially, while Argentina appears to have resisted ceding the field institutional space. Nonetheless, its presence in both countries is strongly palpable; it is clearly a force too strong to be suppressed by resistance from the traditional disciplines.